Severe facial clefting in Insig-deficient mouse embryos caused by sterol accumulation and reversed by lovastatin - Engelking, Luke J. (American Society for Clinical Investigation, 2006)
Insig-1 and Insig-2 are regulatory proteins that restrict the cholesterol biosynthetic pathway by preventing proteolytic activation of SREBPs and by enhancing degradation of HMG-CoA reductase. Here, we created Insig–double-knockout (Insig-DKO) mice that are homozygous for null mutations in Insig-1 and Insig-2. After 18.5 days of development, 96% of Insig-DKO embryos had defects in midline facial development, ranging from cleft palate (52%) to complete cleft face (44%). Middle and inner ear structures were abnormal, but teeth and skeletons were normal. The animals were lethargic and runted; they died within 1 day of birth. The livers and heads of Insig-DKO embryos overproduced sterols, causing a marked buildup of sterol intermediates. Treatment of pregnant mice with the HMG-CoA reductase inhibitor lovastatin reduced sterol synthesis in Insig-DKO embryos and reduced the pre-cholesterol intermediates. This treatment ameliorated the clefting syndrome so that 54% of Insig-DKO mice had normal faces, and only 7% had cleft faces. We conclude that buildup of pre-cholesterol sterol intermediates interferes with midline fusion of facial structures in mice. These findings have implications for the pathogenesis of the cleft palate component of Smith-Lemli-Opitz syndrome and other human malformation syndromes in which mutations in enzymes catalyzing steps in cholesterol biosynthesis produce a buildup of sterol intermediates.